2003
DOI: 10.1097/00005537-200312000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Candidate's Thesis: Platelet‐Activating Factor–Induced Hearing Loss: Mediated by Nitric Oxide?

Abstract: This study demonstrated that PAF placed on the RWM induced hearing loss and cochlear hair cell damage. The PAF-antagonists and L-NAME prevented the PAF-induced hearing loss and inhibited iNOS expression in the cochlea. These findings suggest that the PAF-induced hearing loss caused by cochlear hair cell damage may have been mediated by NO. PAF-antagonists and L-NAME may have future therapeutic implications in preventing sensorineural hearing loss associated with chronic otitis media. The results of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In contrast to these scattered reports for the constitutive forms of NOS, upregulation of iNOS has been demonstrated in many forms of cochlear pathology, including hearing loss due to hypoxia (94,191,205,311), middle ear infection (248,276,319), inflammation (109,204,213,303,306,331), and Ménière disease (120,121,198). Increases in iNOS activity have been observed in the stria vascularis following administration of many ototoxins, including cisplatin (164,320,321), gentamycin (274), aminoglycosides (169), and carbon monoxide (41).…”
Section: Nos and Cochlear Pathologymentioning
confidence: 99%
“…In contrast to these scattered reports for the constitutive forms of NOS, upregulation of iNOS has been demonstrated in many forms of cochlear pathology, including hearing loss due to hypoxia (94,191,205,311), middle ear infection (248,276,319), inflammation (109,204,213,303,306,331), and Ménière disease (120,121,198). Increases in iNOS activity have been observed in the stria vascularis following administration of many ototoxins, including cisplatin (164,320,321), gentamycin (274), aminoglycosides (169), and carbon monoxide (41).…”
Section: Nos and Cochlear Pathologymentioning
confidence: 99%
“…in purulent MEEs. 6 Rhee et al 4 Platelet activating factor is a potent mediator of neutrophil activation leading to calcium mobilization, chemotaxis, aggregation, degranulation, and Mean thickness of middle ear mucosa. Middle ear mucosa ofLPS group was significantly thicker than those of2 control groups.…”
Section: Discussionmentioning
confidence: 99%
“…It can cause pathological changes, including mucosal hyperplasia, bone erosion, fibrosis, and hearing loss. [4][5][6] For the treatment of MEE, Jeon et al? and Lee et al 8 demonstrated that an inhibitor of TNF-a, TNF soluble receptor type I (sTNFRI), prevents experimental otitis media with effusion (OME).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation